KOMITMEN GURU SMP NEGERI KECAMATAN 2X11 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Mairika Pitrawati (Universitas Negeri Padang, 2013)
This research aimed to describeteachers commitment to student, teachers commitment to school, teachers commitment to the task and teachers commitment in Smp Negeri Kecamatan 2 X 11Enam Lingkung Kabupaten Padang Pariaman. The population areall of teacherinSmp Negeri Kecamatan 2 X 11Enam Lingkung Kabupaten Padang Pariamanamount to 84 people and the samplesare68 people that determined based on Krejcie table. Instrument usedwas a questionnaire based on likert scale and analyzed by average score formula. The results areteachers commitmentin Smp Negeri Kecamatan 2 X 11Enam Lingkung Kabupaten Padang Pariaman is good. Key Word : komitmen guru